Guide to WIPO's services for country code top-level domain registries. (World Intellectual Property Organization, Arbitration and Mediation Center, 2022)
This guide presents country code top-level domain (ccTLD) registry operators and national authorities with information on how to resolve third-party domain name disputes in a cost- and time-saving manner. It explains the main policy design features of a successful Alternative Dispute Resolution (ADR) system, and provides information on the WIPO-created Uniform Domain Name Dispute Resolution Policy (UDRP), including the possibility to tailor the UDRP for specific ccTLD requirements. -- page 3.
Keywords: Internet domain names.; Dispute resolution (Law); Règlement de conflits.; Internet domain names